2014
DOI: 10.1007/s10439-014-1121-6
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Biomechanical Effects of Compression Therapy on Deep Veins Using Finite Element Modelling

Abstract: Clinicians generally assume that Medical Compression Stockings (MCS) work by reducing vein luminal diameter and, in this way, help to prevent blood pooling. Conflicting results have been reported however in the case of lower leg deep veins which call into question this hypothesis. The purpose of this contribution is to study the biomechanical response of the main lower leg deep veins to elastic compression and muscle contraction with the objective of improving our current understanding of the mechanism by whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 29 publications
1
48
0
Order By: Relevance
“…Then, studies started to consider the deformation of veins in these models [8], [9], [13]. Recent studies [14] have shown that the biomechanical action and the benefits of elastic compression are different for deep veins and for superficial veins (see Fig. 1).…”
Section: B Motivations For Looking At Superficial Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, studies started to consider the deformation of veins in these models [8], [9], [13]. Recent studies [14] have shown that the biomechanical action and the benefits of elastic compression are different for deep veins and for superficial veins (see Fig. 1).…”
Section: B Motivations For Looking At Superficial Tissuesmentioning
confidence: 99%
“…Indeed, at active muscle state, the intramuscular pressure in the tissues surrounding deep veins varies by range ten times larger than the pressure applied by MCS. The direct impact of elastic compression on the caliber of deep veins is then relatively limited, especially in the standing position [14]- [16]. The situation is different for 0018-9294 © 2014 IEEE.…”
Section: B Motivations For Looking At Superficial Tissuesmentioning
confidence: 99%
“…23,27 Numerous studies have proven the effect of compression therapy on venous and lymphatic system, 1,19,31 whether compression is performed with bandages or stockings. 5 The efficacy of the treatment mainly depends on the level of pressure which is applied on the limb.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it appears that the elastic compression has a significant effect on these veins, whereas the effect on deep veins is rather negligible compared to the effect of muscle contraction [14,15].…”
Section: Assumptions About the Anatomymentioning
confidence: 99%
“…A review is presented in [10]. Previous biomechanical studies [12,13,14] highlighted the importance of inter-individual variations and the necessity to develop computational models on a patient-specific basis. This is the objective of the current chapter.…”
Section: Objectivesmentioning
confidence: 99%